IMPROVING STUDENTS’ WRITING SKILL BY USING STIRRED WORD AND S - Aisiyah Furqoni Rizki; Bambang Harmanto; Niken Reti Indriastuti (Universitas Muhammadiyah Ponorogo, 2018)
Stirred Word and Sentences is a strategy that used to improve students’ writing skill for eighth grade students of MTs. Ma’arif Sukosari. The purpose of this research was to find out how the improvement of students’ writing skill by using Stirred Word and Sentences for the eighth grade students of MTs. Ma’arif Sukosari in academic year 2017/2018. The subject of this research was students of the eighth grade class VIII B in MTs. Ma’arif Sukosari which consisted of 15 students. This research was conducted Classroom Action Research (CAR) that consisted of two cycles, in each cycle consisted of two meetings and four stages, there were: planning, acting, observing and reflecting. The researcher used three instruments in this research, there were: Observation Checklist, Questionnaire and Test. Based on the result of this research, the implementation of Stirred Word and Sentences could improve students’ writing skill at the eighth grade students of MTs. Ma’arif Sukosari in academic year 2017/2018. It was seen from the result of Observation Checklist was 55 % in cycle I up to 85 % in cycle II, it meant the students was active. The questionnaire’s result showed that the students were interested in this method. It can be seen from total of questionnaire I was 66.7 % and the questionnaire II was 91.1 %. The students’ percentage who reached minimum standard of passing grade in cycle I was 53.3 % and in cycle II was 100 %, it meant this research was successful.